STUDI KELAYAKAN USAHATANI KARET (Hevea brasiliensis) DI DESA BUNGA PUTIH KECAMATAN MARANGKAYU KABUPATEN KUTAI KARTANEGARA - Zulfikardy Bardani, Ismail dan Legowo Kamarubayana (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Feasibility Study of Rubber Farming (Hevea brasiliensis) in Bunga Putih Village, Sub district of Marangkayu, Kutai Regency.  This research has been done and achieved purpose, namely, (1) Knowing the cost, revenue and profitability of smallholder rubber farmers per hectare per year in the village of Bunga Putih, Marangkayu district, Kutai Kertanegara regency, namely Fixed Cost (Invest) of Rp 18,430,000.00, and the production of Rp.14,980,000.00 / ha / yr. (2) Knowing the constraints and opportunities in the development of smallholder rubber plants in the study sites, among others: the strategic location of the village, a flat topography, and utilization of rubber tree that does not bear to, building materials , furniture and firewood.The obstacles include: limitations of their knowledge of the management of rubber plantations.(3) Provide a clear picture of the benefits of rubber farmers, using a financial method.(4) Provide input information for the Department of Agriculture in order to be a material consideration in determining policy especially for the continuity of the development of the rubber farmers' efforts, especially in determining the standard price and marketing system.